2014
DOI: 10.1080/02640414.2014.992936
|View full text |Cite
|
Sign up to set email alerts
|

Repeated sprint ability in young basketball players: one vs. two changes of direction (Part 1)

Abstract: The present study aimed to compare the changes of direction on repeated sprint ability (RSA) vs. intensive repeated sprint ability (IRSA) protocols in basketball. Eighteen young male basketball players performed on RSA [10 × 30-m (15 + 15-m, one change of direction)] and IRSA [10 × 30-m (10 + 10 + 10-m, two changes of direction)]. A correlation matrix between RSA, IRSA, "squat jump (SJ)-countermovement jump (CMJ)", footstep analysis and total distance in Yo-Yo intermittent recovery level 1 was performed. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 41 publications
6
39
1
2
Order By: Relevance
“…On the other hand, less information is available about the effect of exercise intensity on FT accuracy. A basketball player might perform FT under situations varying largely for exercise intensity due to the intermittent nature of basketball [11,12], e.g. after rest, when a substitute enters the game and shoots FT or after high-intensity play game.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, less information is available about the effect of exercise intensity on FT accuracy. A basketball player might perform FT under situations varying largely for exercise intensity due to the intermittent nature of basketball [11,12], e.g. after rest, when a substitute enters the game and shoots FT or after high-intensity play game.…”
Section: Introductionmentioning
confidence: 99%
“…However, while data are available for sprint competition, performance disparities between West Sub-Saharan African and Caucasian athletes in response to repeated sprint (RS) are sparsely studied. Definitely, repeated-sprint ability (RSA) is an important fitness component for the team-sport athletes (Padulo et al 2015). Team-sports have a high sequences of repeated short high-intensity efforts (i.e.…”
mentioning
confidence: 99%
“…
IntroductionThe research on the physical determinants of basketball performance from a physiological perspective has focused on profiling of physical fitness characteristics of elite players [1][2][3][4][5][6] . It has been suggested that elite basketball players should have high stature and increased anaerobic power 7,8 .
…”
mentioning
confidence: 99%